Strategi Pemasaran Sosis Solo: Analisis Perilaku Konsumen Dan Upaya Pengembangan Di Era Modern - Suci Rahayu (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Traditional food is an important part of Indonesia's cultural heritage that has great potential to be developed in the modern culinary industry. One example is Sosis Solo, a typical snack from Surakarta that has a distinctive flavor and cultural appeal. However, amidst the onslaught of fast food and instant consumption trends, the existence of traditional foods such as Sosis Solo faces challenges in reaching today's consumers, especially the younger generation. Based on the previous literature review, it is known that the consumption patterns and behaviors of Indonesian consumers show an interest in foods that have cultural value but are still practical and modern. This research uses a qualitative approach to examine Sosis Solo marketing development strategy through STP (Segmenting, Targeting, Positioning) analysis, SWOT, 4P marketing mix (Product, Price, Place, Promotion), and customer insight. The results of the discussion show that the adaptation of modern packaging, digital-based distribution, local value-based promotion, and cultural storytelling approach can increase public buying interest in this product. These findings are expected to be a reference for MSME players to design marketing strategies that are relevant, sustainable, and based on local wisdom.